2020
DOI: 10.3390/ma13132926
|View full text |Cite
|
Sign up to set email alerts
|

The Possibility of Applying Acoustic Emission and Dynamometric Methods for Monitoring the Turning Process

Abstract: Ensuring optimal turning conditions has a huge impact on the quality and properties of the machined surface. The condition of the cutting tool is one of the factors to achieve this goal. In order to control its wear during the turning process, monitoring was used. In this study, the acoustic emission method and measure of cutting forces during turning were used for monitoring that process. The research was carried out on a universal lathe center (CU500MRD type) using a Kistler dynamometer with assemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…There are terms used in technology such as: "process monitoring", e.g. using acoustic emission [2][3][4] and "trouble diagnosis" [5] in relation to changes occurring in time (variable over time) during objects machining. In such an approach, the diagnosis process can be indicated as diagnosing a condition of the process.…”
Section: Introductionmentioning
confidence: 99%
“…There are terms used in technology such as: "process monitoring", e.g. using acoustic emission [2][3][4] and "trouble diagnosis" [5] in relation to changes occurring in time (variable over time) during objects machining. In such an approach, the diagnosis process can be indicated as diagnosing a condition of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Dinde and Dhende 19 investigated the turning of super duplex stainless steel and obtained the optimal combination of parameters for the cutting speed of 120 m/min and back cutting depth of 2.0 mm. Dudzik and Labuda 20 set a cutting depth of 2.0 mm in the turning process. Tekıner and Yeşılyurt 21 studied the turning of austenitic stainless steel with feed rate ranging from 0.2 to 0.3 mm/r and found the feed rate of 0.25 mm/r had the best results.…”
Section: Methodsmentioning
confidence: 99%
“…According to results, they observed that the wiper cubic boron nitride insert significantly reduced TW. Dudzik et al [ 137 ], during the turning process on 304L stainless steel, observed by comparing the AE signals and CFs to predict TW, that both main variables are important in predicting TW. Twardowski et al observed the TW of 100Cr6 steel with the turning process in their study.…”
Section: Indirect Tool Condition Monitoring Systemsmentioning
confidence: 99%